Da escultura tradicional à modelagem 3D: aspectos históricos, técnicos e patrimoniais da arte pública - Fernandes, João Victor Silva (2024)
This dissertation investigates the relationship between techniques, the evolution of tools, and new technologies that permeate the classical and contemporary sculptural process, while exploring connections between art and cultural memory within the urban ecosystems of Espírito Santo, with an emphasis on the Centro-Oeste region. This work is rooted in the extension project "Urban Ecosystems and Culture: Between Memory, Art, and History in the Training of Basic Education Teachers in the Centro-Oeste of Espírito Santo," which, over a year, promoted various educational actions focused on preserving local history. Based on the digital recreation of monuments through 3D modeling and printing, and the adaptation of these elements into pedagogical tools, such as the thematic chessboard, the study seeks to deepen the connection between the miniatures produced and the regional cultural heritage, promoted by the practice of collecting. Moreover, the research also addresses the impact of these initiatives on the transmission of heritage values and the strengthening of regional identity, reflecting on how art, combined with objects of affection, can serve as a link between past and present, valuing the cultural diversity and collective memory of Espírito Santo.